2023
DOI: 10.1088/2053-1591/acfd0c
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, chemical, tensile and morphological characterization studies of bamboo fibre extracted from the indian species bambusa bambos

Suresh Sethu,
Mayandi Kalimuthu,
Rajini Nagarajan
et al.

Abstract: Nowadays, the need for biobased materials is inevitable due to the effective implementation of sustainability concepts. Bamboo fibers have great potential to widen their application range due to their low density and high strength properties. Hence, this study investigates the chemical, mechanical, thermal, and morphological characteristics of untreated and alkaline (NaOH) treated bamboo fibers extracted from bambusa bamboo Indian species. Different instrumental methods, such as thermogravimetric analysis (TGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This is due to the evaporation of the moisture and low molecular substances of waxes and fats in both fibres since the measured moisture content in the chemical composition of CS fibre is 8.35%. This is a common decomposition stage noticed in all natural fibres such as cotton, jute, hemp, bamboo, and coir [28]. At the end of stage 2, the weight loss percentages of the untreated and treated were 70% and 65%, respectively.…”
Section: Mechanical Characterization: Single Fibre Tensile Strength Testmentioning
confidence: 95%
See 2 more Smart Citations
“…This is due to the evaporation of the moisture and low molecular substances of waxes and fats in both fibres since the measured moisture content in the chemical composition of CS fibre is 8.35%. This is a common decomposition stage noticed in all natural fibres such as cotton, jute, hemp, bamboo, and coir [28]. At the end of stage 2, the weight loss percentages of the untreated and treated were 70% and 65%, respectively.…”
Section: Mechanical Characterization: Single Fibre Tensile Strength Testmentioning
confidence: 95%
“…The core component of CS fibre cell walls is cellulose, typically in the form of fibrils, which are mainly composed of three elements: carbon, hydrogen, and oxygen. Cellulose contents of untreated CS fibres were found to be 73.13%, on par with bamboo, jute, hemp, sisal, and cotton but lower than coir fibres [28]. Cellulose content influences strength, durability, and thermal stability, making it suitable for heat resistance applications.…”
Section: Chemical Characterization: Chemical Compositions Of Cs Fibresmentioning
confidence: 97%
See 1 more Smart Citation
“…The fibers of different bamboo species have been studied by various scholars. Sethu et al (2023) studied the thermal and chemical properties of a particular bamboo species in India and found that its bamboo fiber can be used as an effective reinforcement unit for the development of polymer-based composites in the automotive and construction industries. Sikam et al (2021) studied the physicochemical and mechanical properties of Bambusa vulgaris (BV) fiber, which is common in Cameroon, and pointed out that BV fiber can be used as a reinforcement material in the textile or construction fields.…”
Section: Introductionmentioning
confidence: 99%